Public Perception on the Implementation of PON XXI Event North Sumatera-Aceh at Situngkir Panguruan Beach in 2024 - Zuhriyah Zuhriyah; Azadeh Zarei; Louie Peter Gula; Samsuddin Siregar (Inspiree)
The  purpose  of  the study. This study aimed to evaluate public perception regarding the implementation of PON XXI Event North Sumatra-Aceh at Situngkir Panguruan Beach in 2024, focusing on economic impact, infrastructure development, environmental considerations, and cultural integration. The research examined community attitudes toward event implementation and its implications for local development.